A Risk-Based Assessment to Advise the Responsible Consumption of Invertebrates, Elasmobranch, and Fishes of Commercial Interest in Mexico - Saldaña-Ruiz, Luz Erandi; Flores-Guzmán, Alesa; Cisneros-Soberanis, Frida; Cuevas-Gómez, Gabriela Alejandra; Gastélum-Nava, Ernesto; Rocha-Tejeda, Lorena; Chavez, Jose Francisco; Hernandez-Pimienta, Raziel Elihu; Fernández-Rivera Melo, Francisco Javier (Frontiers in Marine Science, 2022)
The main key drivers of vulnerability for marine species are anthropogenic stressors, ranging from pollution and fishing to climate change. The widely documented impacts of fishing activities on marine species, the growing concern about the population status of many marine species, and the increase in per capita consumption of marine products worldwide have led to the development of environmentally responsible fishing standards and initiatives to inform consumers about the health status of the species. In Mexico, fishing is a vital source of jobs and food security for many coastal communities, but the population status of many species of commercial importance has not been evaluated. Management efforts and fisheries certification procedures and standards to achieve the sustainability of many Mexican fisheries are hindered by a lack of biological and fishery data for many species. In this study, a risk assessment methodology for data-limited fisheries, a Productivity, and Susceptibility Analysis was used to estimate the relative vulnerability of marine invertebrates and fishes commercially important in Mexico to fishing. Ninety-eight invertebrates, 66 elasmobranchs, and 367 bony fish were analyzed. The vulnerability among the 531 evaluated species is high for 115 (22%), moderate for 113 (21%), and low for 303 (57%). The most vulnerable species are the Mexican geoduck (Panopea globosa) and the Black Sea Cucumber (Holothuria atra) for invertebrates, the Spiny butterfly ray (Gymnura altavela) among elasmobranches, and the Black-and-yellow rockfish (Sebastes chrysomelas) for bony fishes. This study provides a first screening of the many species potentially affected by fisheries, prioritizes marine species for future research and management efforts, identifies the main data gaps, and sets the baseline for future research efforts and management. Furthermore, the results could improve market-based approaches like eco-labeling initiatives and the Responsible Seafood Consumption Guide, developed by Mexican authorities in collaboration with Comunidad and Biodiversidad (COBI, a civil society organization), to inform consumers about the origin and sustainability of fishery products.